Estimating a Model of Qualitative and Quantitative Education Choices in France - Christian Belzil; François Poinas (Institute of Labor Economics (IZA), 2018)
We estimate a structural model of education choices in which individuals choose between a professional (or technical) and a general track at both high school and university levels using French panel data (Génération 98). The average per-period utility of attending general high school (about 10,000 euros per year) is 20% higher than that of professional high school (about 8000 euros per year). About 64% of total higher education enrollments are explained by this differential. At the same time, professional high school graduates would earn 5% to 6% more than general high school graduates if they both entered the labor market around age 18. The return to post-high school general education is highly convex (as in the US) and is reaped mostly toward the end of the higher education curriculum. Public policies targeting an increase in professional high school enrollments of 10 percentage points would require a subsidy of 300 euros per year of professional high school.
Keywords: C51; I23; I26; J24; 330; education choices; returns to schooling; professional education; structural model